Evaluation of the hypothesis of the Monster of Troy vase as the earliest artistic record of a vertebrate fossil - Monge-Nájera, Julián (Uniciencia, 2020)
The Monster of Troy, depicted in a 6th Century BC Corinthian vase, has been proposed to be the earliest artistic record of a vertebrate fossil, possibly a Miocene giraffe (Samotherium sp.). The purpose of the paper was to analyze the giraffe hypothesis using four approaches: a double-blind random design in which 78 biologists compared the vase skull with Samotherium and several reptiles; an informed survey of 30 art and science students who critically assessed the hypothesis based on images of candidate species; an objective computerized mathematical comparison of the images; and a detailed morphological comparison of the skulls. All of the participants rejected the giraffe hypothesis. The types of eyes and teeth unambiguously discard a mammal, whether fossil or living, as the model. The model was most likely an extant carnivorous reptile of the Varanidae family.